Schooling and immunization of orphaned children in Swaziland - LEE, Yu-Ra (KDI School, 2016)
Swaziland is a HIV/AIDS prevalent country, with the highest affected rate in the world. As a result, the number of orphans has increased over the years. This paper strives to find factors to eliminate inequality in Swazi orphans in education and health. Children from six to fifteen years of age are selected to examine the effect of household wealth and mother’s education level on the enrollment ratio and whether a child is in the officially recommended grade for his/her age in school or not (n=2,970), using logistic regression. Furthermore, children between zero and five years are chosen to see the effect of an immunization card on the number of vaccinations: BCG, polio, and DPT/HepB/Hib (n=1,393) with zero-inflated regression. The data used is from the Swaziland Multiple Indicator Cluster Survey (MICS) in 2010. Although wealth does not significantly affect the education of non-orphans statistically, it becomes more important to orphans along with mother’s education level. An immunization card solves the health inequality of orphans in the number of vaccination in Swaziland. These results imply that the country is recommended to enforce policies on education differently by group and to encourage people to use immunization cards to remove the inequality in education and health caused by loss of parents.
Thesis(Master) --KDI School:Master of Development Policy,2016